2021
DOI: 10.1002/pri.1915
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Portuguese physiotherapists during COVID‐19 pandemic

Abstract: Objective This study described the burnout experienced by physiotherapists during the COVID‐19 pandemic and analysed the role of possible factors of this occupational phenomenon. Methods Cross‐sectional study based on a web‐based survey applied to physiotherapists living in Portugal. The survey included sociodemographic, health status and clinical practice questions. The Copenhagen Burnout Inventory (personal, work‐ and patient‐related burnout), the Resilience Scale, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 45 publications
4
28
1
7
Order By: Relevance
“…In Portugal, the physiotherapy population was estimated to be 12,891 (World Confederation for Physical Therapy, 2019a), so this sample is approximately 3.51% of the total estimated population. Also keeping with published studies regarding physiotherapists in Portugal (Jácome et al., 2021). Although these small sample sizes have allowed us to explore the survey tool and relationships between variables, we should be cautious that is the results of this study are preliminary, focussed on those that had a specific interest in falls and an ageing population, and cannot be generalised to the wider physiotherapy population in each country.…”
Section: Discussionsupporting
confidence: 84%
“…In Portugal, the physiotherapy population was estimated to be 12,891 (World Confederation for Physical Therapy, 2019a), so this sample is approximately 3.51% of the total estimated population. Also keeping with published studies regarding physiotherapists in Portugal (Jácome et al., 2021). Although these small sample sizes have allowed us to explore the survey tool and relationships between variables, we should be cautious that is the results of this study are preliminary, focussed on those that had a specific interest in falls and an ageing population, and cannot be generalised to the wider physiotherapy population in each country.…”
Section: Discussionsupporting
confidence: 84%
“…In the study of Khasne et al, conducted among 2026 healthcare workers in India, greater than half of the respondents (1.069; 52.8%) had pandemic related burnout [ 40 ]. The references available in this respect contain a few studies that prove the impact of the COVID-19 pandemic on the level of occupational burnout among physiotherapists [ 41 , 42 ]. The study carried out during the pandemic among Portuguese physiotherapists showed that more than 40% of them experienced personal and work related burnout and 25% patient related burnout, with resilience, depression and stress having a relevant role in the three burnout dimensions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The references available in this respect contain a few studies that prove the impact of the COVID-19 pandemic on the level of occupational burnout among physiotherapists [ 41 , 42 ]. The study carried out during the pandemic among Portuguese physiotherapists showed that more than 40% of them experienced personal and work related burnout and 25% patient related burnout, with resilience, depression and stress having a relevant role in the three burnout dimensions [ 41 ]. The examination conducted by Pniak et al (2021), in south-east Poland with the use of MBI questionnaire among professionally active physiotherapists working in hospitals, showed that physiotherapists presented high burnout rates in all three dimensions: emotional exhaustion (Mean 32.31; CI 29.47–35.15), depersonalization (Mean 16.25; CI 14.48–18.03) and personal accomplishment (Mean 26.25; CI 24.41–28.10) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Levels of stress were higher in female workers, those with fewer years in their role and those working in inpatient settings. 77 Among physiotherapists, burnout has also significantly increased during the COVID-19 pandemic, 78 , 79 with reports suggesting that physiotherapists who experience the greatest levels of burnout are those working directly with COVID-19 patients and/or working in ICU. 78 , 79 While anxiety can be high amongst staff who have direct contact with people who have COVID-19, staff who believe that their health service's response and staff support strategies are effective may experience lower levels of depression, anxiety and stress.…”
Section: Recommendationsmentioning
confidence: 99%